Reasons for mini-implants failure: choosing installation site should be valued! - Alberto Consolaro; Fábio Lourenço Romano (Dental Press Editora, 2014)
Mini-implant loss is often associated with physical and mechanical aspects that result from choosing an inappropriate placement site. It is worth highlighting that: a) Interdental alveolar bone crests are flexible and deformable. For this reason, they may not offer the ideal absolute anchorage. The more cervical the structures, the more delicate they are, thus offering less physical support for mini-implant placement; b) Alveolar bone crests of triangular shape are more deformable, whereas those of rectangular shape are more flexible; c) The bases of the alveolar processes of the maxilla and the mandible are not flexible, for this reason, they are more likely to receive mini-implants; d) The more cervical a mini-implant is placed, the higher the risk of loss; the more apical a mini-implant is placed, the better its prognosis will be; e) 3D evaluations play a major role in planning the use of mini-implants. Based on the aforementioned considerations, the hypotheses about mini-implant loss are as follows: 1) Deflection of maxillary and mandibular alveolar processes when mini-implants are more cervically placed; 2) Mini-implants placed too near the periodontal ligament, with normal intra-alveolar tooth movement; 3) Low bone density, low thickness and low alveolar bone volume; 4) Low alveolar cortical bone thickness; 5) Excessive pressure inducing trabecular bone microfracture; 6) Sites of higher anatomical weakness in the mandible and the maxilla; 7) Thicker gingival tissue not considered when choosing the mini-implant.